(untitled) (Jurnal Bawaslu Provinsi Kepulauan Riau, 2023)
Digital media has an important role in carrying out life in society, especially in the political field. One area of ​​politics that can utilize digital media is the general election process, but unfortunately, to date, its use has not been maximized. General elections in democratic countries, including Indonesia, are a means used by citizens to elect their representatives in legislative and non-legislative institutions as well as elect the president and other government officials in running the government. This research is a type of normative juridical research, namely recording various important readings and compiling points in the discussion to be researched. By describing the various studies that have been obtained and solving problems related to existing themes. The conclusion obtained is that digital media is currently only used as a means of providing information and various news regarding general elections. Also as a means to further introduce the figures or candidates who are running for leadership. It is hoped that maximum use of digital media can reduce weaknesses in the general elections that will be held in 2024, including minimizing costs and making time efficient, to build a better Indonesia with innovative and quality elections in maintaining the democratic principles of the Indonesian nation.